2013
DOI: 10.1002/bdd.1881
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 haplotype influences the sirolimus dose requirements in Chinese renal transplant recipients

Abstract: Sirolimus, an immunosuppressive drug used to prevent organ rejection after renal transplantation, has a narrow therapeutic index and a large inter-individual variability of pharmacokinetics. The aim of this study was to analyse the dose-normalized trough blood concentrations (C0 /D ratio) of sirolimus in patients with different genotypes and attempt to investigate the possible associations between ABCB1/CYP3A5 genotypes and sirolimus dose requirements in Chinese renal transplant recipients. Blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Therefore, the ABCB1 haplotype (including C1236T, G2677T/A and C3435T) may influence the drug pharmacokinetics more significantly [17,36]. Our previous study [39] focusing on the impact of this ABCB1 haplotype on sirolimus dose requirement demonstrated that the CGC/ CGC diplotype carrier was about 30% lower compared with those carrying the CGC/TTT or TTT/TTT diplotype. The study by Wang also reported that the C 0 /D of CsA was related to the haplotype of ABCB1 [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ABCB1 haplotype (including C1236T, G2677T/A and C3435T) may influence the drug pharmacokinetics more significantly [17,36]. Our previous study [39] focusing on the impact of this ABCB1 haplotype on sirolimus dose requirement demonstrated that the CGC/ CGC diplotype carrier was about 30% lower compared with those carrying the CGC/TTT or TTT/TTT diplotype. The study by Wang also reported that the C 0 /D of CsA was related to the haplotype of ABCB1 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Search strategy. A computerized literature search was conducted to identify relevant articles published up to 30 July 2014in PubMed (1966-2014, Embase (1974Embase ( -2014, Medline (1966-2014) and Cochrane Library databases (Issue 7 2014). To investigate the relationship between ABCB1 C3435T polymorphism and pharmacokinetics of CsA in kidney transplant recipients, the following search terms were used: '(kidney or renal) and (transplantation or transplant or allograft or graft) and (cyclosporine or ciclosporin or cyclosporin) and (MDR1 or MDR-1 or ABCB1 or p-glycoprotein or P-gp) and (polymorphism or polymorphisms or genotype)'.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies on patients with renal transplantation[ 43 , 47 ] did not show any association between the ABCB1 c.3435C>T SNP and the mTORI dose. Another study[ 48 ] found that Chinese patients carrying the ABCB1CGC/CGC haplotype require a lower dose of sirolimus. ABCB1 does not seem to exert any pharmacogenetic effect on the PK of mTORIs.…”
Section: Pharmacogenetics Of Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…Six studies were excluded: 3 articles were non-relevant studies; 1 article supplied insufficient data; 1 article described as log C/D; 1 article investigated the D/C ratio. Thus, there were 6 eligible studies (10,11,(18)(19)(20)(21) described the association of ABCB1 polymorphism with the C/D ratio of SRL. These studies were conducted in different countries including China (10,18,19), Spain (20), Belgium (21), France (11).…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%